2018
DOI: 10.1177/1550059418813034
|View full text |Cite
|
Sign up to set email alerts
|

EEG Neurofeedback Training in Children With Attention Deficit/Hyperactivity Disorder: A Cognitive and Behavioral Outcome Study

Abstract: Background. Attention deficit/hyperactivity disorder (ADHD) is a highly prevalent childhood disorder with symptoms of inattention, impulsivity, and hyperactivity. EEG neurofeedback training (NFT) is a new intervention modality based on operant conditioning of brain activity, which helps reduce symptoms of ADHD in children. Methods and Procedures. To examine the efficacy of NFT in children with ADHD, an experimental longitudinal design with pre-post comparison was adopted. A total of 30 children in the age rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…One Indian study has shown positive effects of NF. [ 57 ] The resource (space in hospitals, money, and trained manpower) crunch may be the major reason for less number of studies in cognitive/neurocognitive interventions in India.…”
Section: Discussionmentioning
confidence: 99%
“…One Indian study has shown positive effects of NF. [ 57 ] The resource (space in hospitals, money, and trained manpower) crunch may be the major reason for less number of studies in cognitive/neurocognitive interventions in India.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis also showed that [17], under the intervention of multiple combinations of moderate-intensity aerobic exercise, ADHD patients' attention deficit can not only be alleviated in the short term but also obtain long-term enhancement effect. However, compared with sport intervention, other nonpharmacological therapies have different mechanisms of action, but their efficacy in practice is also worthy of affirming [18][19][20][21][22][23]. For a long time, there are still differences in the ranking of the advantages and disadvantages of various nonpharmacological therapies in improving ADHD symptoms [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 1 , there are two major attention training models: external stimulation using interesting games [ 12 , 14 , 16 , 17 ], and the use of biofeedback to enhance the effectiveness of concentration exercises [ 13 , 14 ]. On the other hand, the most relevant research for this focused training is mindfulness meditation training [ 8 , 9 , 10 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The field of vision should only contain the item focused on [ 11 ]. Training methods to improve students’ attention include computer games [ 12 ], neurofeedback [ 13 , 14 , 15 ], virtual and augmented reality [ 16 , 17 ], music [ 18 ], and meditation [ 19 ]. Table 1 provides details of these methods.…”
Section: Introductionmentioning
confidence: 99%